Different origin of auditory and phonological processing problems in children with language impairment: evidence from a twin study. - Bishop, D; Bishop, S; Bright, P; James, C; Delaney, T; Tallal, P (1999)
This study investigated the heritability of auditory processing impairment, as assessed by Tallal's Auditory Repetition Test (ART). The sample consisted of 37 same-sex twin pairs who had previously been selected because one or both twins met criteria for language impairment (LI) and 104 same-sex twin pairs in the same age range (7 to 13 years) from the general population. These samples yielded 55 children who met criteria for LI, who were compared with 76 children whose language was normal for their age (LN group). We replicated earlier work showing that group LI is impaired relative to group LN on ART. However, there was no evidence of a heritable influence on ART scores: Correlations between twins and their co-twins were reasonably high for both MZ and DZ twins, suggesting that performance is more influenced by shared environment than genetic factors. Analyses of extreme scores gave a similar picture of nonsignificant group heritability. In contrast, a test of phonological short-term memory, the Children's Nonword Repetition Test (CNRep), gave high estimates of group heritability. In general, CNRep was a better predictor of low language test scores than ART, but ART did make a significant independent contribution in accounting for variance in a test of grammatical understanding.